Ta’līm Mahārat al-Qirā’ah Li Ta’zīzi Fahmi al- Maqru’ fī al-Mawād bi al-Lughat al-‘Arabiyyah - Nur, Ifa Rodifah; Rahmawati, Fitra Awalia (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2020)
Reading skill is one of the fundamental pillars in teaching Arabic to non-native speakers, serving as a primary vehicle for expanding vocabulary, sentence structures, and idiomatic phrases used in both speech and writing. To cultivate this skill, various pedagogical methods and theories are utilized—each presenting its own set of advantages and disadvantages. These traditional and contemporary approaches include the literal method, the phonemic method, the word method, the sentence method, and the association method. Beyond foundational instruction, reading proficiency spans a developmental spectrum ranging from basic decoding to advanced cognitive processing. These levels encompass line-reading skills (literal reading), interlinear reading skills (interpretative reading), behind-line reading skills (creative reading), and the evaluation of textual content (critical reading). Ultimately, the primary objective of the reading process is comprehension; true reading cannot be decoupled from understanding. Despite this, some individuals spend considerable time reading passively without a specific, targeted goal. Because a reader cannot draw valid inferences or derive meaningful benefits without cognitive engagement, understanding remains the indispensable basis of the reading process, rendering reading without comprehension entirely futile.